2013
DOI: 10.1002/asia.201300838
|View full text |Cite
|
Sign up to set email alerts
|

Facile Self‐Assembly of Intermetallic [Ni2Gd2] Cubane Aggregate for Magnetic Refrigeration

Abstract: Cubane Cooler: An intermetallic cubane aggregate shows a pronounced cryogenic magnetocaloric effect (MCE). A mixed‐metal [Ni2Gd2] cubane was assembled by the use of 2‐(hydroxymethyl)pyridine (hmpH) as a spacer in a simple one‐pot reaction. Its MCE measurement gives 34.4 J kg−1 K−1 at 4.5 K, suggesting that, apart from the commonly used large‐nuclearity metal aggregates, smaller metal cubanes can also exhibit a large MCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Gadolinium exhibits paramagnetic properties due to the presence of unpaired electrons, and these electrons realign under external magnetic field leading to an increase in the material's temperature. [12] Upon removal of the magnetic field, the electron paths become unaligned, which eventually leads to cooling of the material. [11] In this study, it was not possible to relate the temperature variations to paramagnetic properties (concentration) of gadolinium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium exhibits paramagnetic properties due to the presence of unpaired electrons, and these electrons realign under external magnetic field leading to an increase in the material's temperature. [12] Upon removal of the magnetic field, the electron paths become unaligned, which eventually leads to cooling of the material. [11] In this study, it was not possible to relate the temperature variations to paramagnetic properties (concentration) of gadolinium.…”
Section: Discussionmentioning
confidence: 99%
“…As the atoms become more aligned, resulting with reduced entropy of the system, the material's temperature rises. [12] Upon removal of the magnetic field, the electron paths become unaligned, which eventually leads to cooling of the material. [11] During this heating and cooling period, heat is exchanged between the gadolinium based contrast agent and its surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Around the same time, Hor et al reported a simple one‐pot self‐assembly of a { Ni2IIGd 2 } heterometallic cubane, 103 ,85a which was stable in CH 2 Cl 2 , as supported by the electrospray ionization mass spectrum. The –Δ S m values of 103 under all fields increase as the temperature drops from 7.5 to 4.5 K, reaching a maximum of 34.4 J kg −1 K −1 for an applied field of 70 kOe at 4.5 K, which is approximately the same as the theoretical maximum –Δ S m value of 37.6 J kg −1 K −1 .…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 98%
“…Based on the above considerations, various 3d‐Ln III cluster‐based‐CPs, serving as molecular magnetic refrigerants, have been extensively synthesized and investigated (Tables and ),68–110,113 including Mn–Ln, Co–Ln, Ni–Ln, Cu–Ln, Cr–Ln, Fe–Ln, and Zn–Ln.…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 99%
See 1 more Smart Citation